2020
DOI: 10.1016/j.fuel.2020.117448
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on ammonia/hydrogen/air combustion in spark ignition engine conditions

Abstract: 8The mitigation of climate change implies the increasing use of variable renewable energy sources. Energy 9 storage and transport solutions will contribute to ensure the stability, reliability and flexibility of the energy 10 systems in that context. Ammonia is a well-known chemical of formula NH3 and, amongst other electrofuels, 11 a promising energy carrier and carbon-free combustible fuel. In the present experimental study, engine per-12 formance, combustion characteristics and pollutant emissions of a rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
120
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 332 publications
(142 citation statements)
references
References 70 publications
9
120
0
Order By: Relevance
“…The set-up is introduced in the dedicated section in the following. The first part of the study aimed at determining the satisfying limits of operation of the present engine in its as-is design in terms of mixture composition and was presented in [29]. Premixed gaseous ammonia/hydrogen/air mixtures with up to 60 vol.% H2 in the fuel were fueled in the engine for equivalence ratios ranging from 0.6 to 1.2.…”
Section: Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The set-up is introduced in the dedicated section in the following. The first part of the study aimed at determining the satisfying limits of operation of the present engine in its as-is design in terms of mixture composition and was presented in [29]. Premixed gaseous ammonia/hydrogen/air mixtures with up to 60 vol.% H2 in the fuel were fueled in the engine for equivalence ratios ranging from 0.6 to 1.2.…”
Section: Speciesmentioning
confidence: 99%
“…The experiments with NH3/H2/air mixtures show that H2 mainly acts as an ignition promoter during the initiation phase when small fractions are added [30]. Further enrichment then significantly accelerates the combustion phases, as the effect of hydrogen on the combustion properties is becoming more important [29]. Therefore, the assumption of partial thermal NH3 dissociation to H2 and N2 in the fresh gases under the combined effect of the compression and the spark could explain the successful engine operation with pure NH3, in spite of unfavorable combustion properties.…”
Section: Combustion Analysismentioning
confidence: 99%
“…At the moment, there are quite a lot of studies in the field of reducing harmful emissions of internal combustion engines, these include mixing hydrogen fuel [1,3,10,12], using modern water injection control systems [2], swirling the flow [4], diluting various types of fuel with liquefied gas [5] or methane [6], diesel [7], catalysis [8], gas recirculation [9], "poor" burning [11].…”
Section: Thematic Scope: Publication Of Papers On Geology and Technical Sciencesmentioning
confidence: 99%
“…Pochet et al 17 reported on engine experiments using ammonia and hydrogen mixtures in Homogeneous Charge Compression Ignition (HCCI) combustion mode. Lhuillier et al 18 recently reported engine experiments of ammonia and hydrogen mixtures under spark-ignition engine conditions. Ammonia has also been demonstrated in modern compression ignition engines in combination with conventional diesel fuel oil, used for ignition.…”
Section: Introductionmentioning
confidence: 99%